Anesthetic Considerations in Facial Transplantation: Experience at NYU Langone Health and Systematic Review - Alfonso, Allyson R. (Plast Reconstr Surg Glob Open, 2020)
Anesthetic considerations are integral to the success of facial transplantation (FT), yet limited evidence exists to guide quality improvement. This study presents an institutional anesthesia protocol, defines reported anesthetic considerations, and provides a comprehensive update to inform future directions of the field. METHODS: An institutional “FT Anesthesia Protocol” was developed and applied to 2 face transplants. A systematic review of 3 databases captured FTs in the peer-reviewed literature up to February 2020. Two reviewers independently screened titles and abstracts to include all clinical articles with FT recipient and/or donor-specific preoperative, intraoperative, and relevant postoperative anesthetic variables. Data charting guided a narrative synthesis, and quantitative synthesis reported variables as median (range). RESULTS: Our institutional experience emphasizes the importance of on-site rehearsals, anticipation of patient-specific anesthetic and resuscitative requirements, and long-term pain management. Systematic search identified 1092 unique records, and 129 met inclusion criteria. Reports of 37 FTs in the literature informed the following anesthetic axes: donor pre- and intraoperative management during facial allograft procurement, recipient perioperative care, immunotherapy, antimicrobial prophylaxis, and pain management. Quantitative synthesis of 30 articles showed a median operative time of 18 hours (range, 9–28) and fluid replacement with 13 L (5–18) of crystalloids, 13 units (0–66) of packed red blood cells, 10 units (0–63) of fresh frozen plasma, and 1 unit (0–9) of platelets. CONCLUSIONS: Anesthetic considerations in FT span the continuum of care. Future efforts should guide standard reporting to establish evidence-based strategies that promote quality improvement and patient safety.